Penerapan Laplacian of Gaussian Dalam Mendeteksi Tepi Luka Bakar Pada Manusia - Gulo, Hasanuddin (TIN: Terapan Informatika Nusantara, 2020)
Burns are tissue damage caused by contact with high temperatures such as fire, hot water, electricity, chemicals, and radiation. Image edge detection is an important part of radiotherapy because this process is the first step in separating objects in images that have different characteristics and characteristics. The boundary between one object and another object in an image with different characteristics is clear, then the medical image can be further analyzed and also the patient's disease condition diagnosis is seen by interpreting the medical image without having to perform surgery. Edge detection is performed using Laplacian of Gaussian, this operator will capture edges from all directions and produce sharper edges.